2018
DOI: 10.1371/journal.pone.0201102
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perception of smile esthetics and orthodontic treatment in Spanish patients

Abstract: One of the main objectives of orthodontic treatment is to achieve an esthetic smile. This study set out to analyze differences in the perception of smile esthetics among patients before and after receiving orthodontic treatment. 250 Spanish patients analyzed a single photograph in which, by means of computer software, midline diastema, black triangle, gingival margin of the left central incisor, and gingival (“gummy”) smile were altered. Each patient analyzed these images before and after undergoing orthodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…It has been reported that missing anterior teeth had a significant negative effect on the perception of esthetic [ 30 , 31 ]. In contrast, orthodontic treatment or orthognathic/plastic surgery had a significant positive effect on esthetic perception [ 32 ]. We excluded subjects with these features or treatments to avoid any confounding factors that might affect their esthetic perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that missing anterior teeth had a significant negative effect on the perception of esthetic [ 30 , 31 ]. In contrast, orthodontic treatment or orthognathic/plastic surgery had a significant positive effect on esthetic perception [ 32 ]. We excluded subjects with these features or treatments to avoid any confounding factors that might affect their esthetic perception.…”
Section: Discussionmentioning
confidence: 99%
“…perception [32]. We excluded subjects with these features or treatments to avoid any confounding factors that might affect their esthetic perception.…”
Section: Plos Onementioning
confidence: 99%
“…Visual perception is a condition for appreciation of what is beautiful, and can readily detect what is out of harmony and balance [2,3]. This fact creates a challenge for the professional, who must apply their knowledge in the elaboration of a scientifically adequate treatment plan, and at the same time, positively meet the esthetic expectations of the patient and obtain the observers' approval [2,4].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Few recent studies have recently re-evaluated the question whether dental education has a significant effect on one's aesthetic perception. 13,14,15 Whilst each study provided ample data and evaluation, none of these above studies compared dental students to medical students in the same cohort, who would be of similar age, social and cultural norms and gender. These are influential factors for the perception of smile aesthetics.…”
Section: Introductionmentioning
confidence: 99%